Achievable Rates for Full-Duplex Massive MIMO Systems Over Rician Fading Channels - Juan Liu (IEEE Access, 2018)
We study the uplink and downlink achievable rate of full-duplex large-scale multi-input multioutput (MIMO) systems with a base station (BS) and users over Rician fading channels, based on maximum ratio combining/maximum ratio transmission and zero-forcing reception/zero-forcing transmission processing. Contrary to previous related works over Rayleigh fading channels, this paper assumes that the fast fading MIMO channel matrix follows the Rice distribution which will be more common in future 5G wireless communication systems. We derive approximate expressions of the uplink and downlink achievable rate for perfect channel state information when the number of BS antennas grows large. Based on the theoretical analysis, it is found that when the antennas of the BS are large enough and the power scaling law is applied properly, the impact of multi-user interference, loop interference, inter-user interference, and noise can be suppressed. In addition, the simulation results show that the uplink and downlink achievable rates increase with the number of BS antennas and they will converge to fixed values with the increasing Rician K-factor.